Quality In A Property Development Project : A Case In Rusunami Kalibata City - Bahar, Sabrina; Firman, Aries F (The Indonesian Journal of Business Administration, 2012)
Rusunami of Kalibata Residence is one of 3 (three) residences group at Kalibata City Super Block area at Kalibata, South of Jakarta that is developed by AgungPodomoro Group as a respond to government program of 1000 tower Rusunami/Rusunawa in Indonesia. Consist of 7 towers that now already complete its construction, it has been lived in by tenants and now at operation management step. Rusunami as the name “ RumahSusunSederhanaHakMilik “ is property business as like apartment that have unique characteristic of business, because combination of product delivered and service quality with no direct repeat order activity. There are three main business, project management at development step, marketing at promotion and transaction step and property operation management as after sales service at normal operation. At the operation management step, the main objective of business is to ensure customer that staying at Kalibata Residence is satisfy for all of product and service delivered. It should cover all customer main needs and the promised thing at marketing promotion step. The main business issue also related to the main objective, it is unsatisfied respond from customer of product and service quality delivered. The cost of unsatisfied impact will be more expensive that cost of best service quality. Based on observation and research at the field, the source of unsatisfied customer come from quality of product and service accepted compare their expectation. There are some expectation the people to by and stay at Kalibata Residence as his need and concept of live, it is also be stronger by marketing promised from developer. Developer already delivered the room unit tenant /customer and make service quality program of daily operation management to comply the customer expectation and developer promised. So the main source can come from high expectation of customer and there are some quality problem the product and service delivered. As property operation management should respond this issue to achieve the business objective, increase customer satisfaction.The recommended solution is quality service improvement at all dimensions of service quality (tangible, responsiveness, reliability, performance and empathy) with priority based on the breakdown of unsatisfied customer respond and timing schedule.   Keywords: quality of property, service quality